Pre-Service Chemistry Teacher Ability in Constructing Content Representation on Electrochemistry Based Context - Antuni Wiyarsi; Muhd Ibrahim Muhamad Damanhuri (Universitas Sarjanawiyata Tamansiswa, 2021)
The study aims to explore the pre-service chemistry teacher ability in constructing Content Representation (CoRe) on electrochemistry based context. This research adopted an instrumental case study. A total of 20 pre-service chemistry teacher enrolled on Curriculum course were the subject of this research. The data of pre-service chemistry teacher ability in constructing CoRe were collected according to the document which consist a questions on pedagogical aspect. There were 9 indicators were used as a references to explored the pre-service chemistry teacher ability in constructing CoRe. The data of pre-service chemistry teacher ability in constructing CoRe were analysed according to descriptive quantity technique by classifying the mean score obtained into five categories from very good to very poor. The result of this study showed that the pre-service chemistry teacher ability in constructing CoRe were pretty good, thus it can be concluded that pre-service chemistry teacher were ready to conducted a quality chemistry learning. The pre-service chemistry teacher in the future is expected applying CoRe in every learning to promote students’ chemistry meaningful learning.